Species-specific or assemblage-wide decline? The case of Arthroleptides dutoiti Loveridge, 1935 and the amphibian assemblage of Mount Elgon, Kenya. Issue 1 (2nd January 2021) - Ngwava, Jacob M; Barratt, Christopher D; Boakes, Elizabeth; Bwong, Beryl A; Channing, Alan; Couchman, Olivia; Lötters, Stefan; Malonza, Patrick K; Muchai, Vincent; Nguku, Julius K; Nyamache, Joash; Owen, Nisha; et al.
ABSTRACT: The frog Arthroleptides dutoiti Loveridge, 1935, endemic to Mount Elgon, East Africa was last collected in 1962 and has not been observed since. The species is regarded as Critically Endangered by the IUCN Red List and is a priority species on the Zoological Society of London's EDGE (Evolutionarily Distinct, Globally Endangered) project, given its Red List status and phylogenetic distinctiveness. We analyse temporal patterns of abundance (1934–2014) of A. dutoiti and the remainder of the Mount Elgon amphibian assemblage to infer the probability of re-encountering A. dutoiti and assess whether declines are species specific to A. dutoiti, or whether they are assemblage-wide phenomena. Our results show that for localities where surveys have been repeatedly conducted, A. dutoiti is likely to be locally extinct. Declines are observed in other Mount Elgon amphibians, encompassing both specialists and generalists. Causal factors for declines are unknown, but habitat change might be important, given the high degree of forest loss in the area, especially since the turn of the 20th century. Urgent sampling of preferred microhabitats of A. dutoiti at the type locality and surrounding areas beyond those included in our study are required to determine whether or not the species is extinct. Impacts on other taxonomic groups would also be useful to understand so that it can be determined how broad the changes are for the Mount Elgon biota.